Human Induced Pluripotent Stem Cell-Derived Pericytes as Scalable and Editable Source to Study Direct Lineage Reprogramming Into Induced Neurons - Menon, Radhika; Petrucci, Linda; Lohrer, Benjamin; Zhang, Jingzhong; Schulze, Markus; Schichor, Christian; Winner, Beate; Winkler, Jürgen; Riemenschneider, Markus J.; Kühn, Ralf; Falk, Sven; Karow, Marisa (Cellular Reprogramming, 2023)
Studying human somatic cell-to-neuron conversion using primary brain-derived cells as starting cell source is hampered by limitations and variations in human biopsy material. Thus, delineating the molecular variables that allow changing the identity of somatic cells, permit adoption of neuronal phenotypes, and foster maturation of induced neurons (iNs) is challenging. Based on our previous results that pericytes derived from the adult human cerebral cortex can be directly converted into iNs (Karow et al., 2018; Karow et al., 2012), we here introduce human induced pluripotent stem cell (hiPSC)-derived pericytes (hiPSC-pericytes) as a versatile and more uniform tool to study the pericyte-to-neuron conversion process. This strategy enables us to derive scalable cell numbers and allows for engineering of the starting cell population such as introducing reporter tools before differentiation into hiPSC-pericytes and subsequent iN conversion. Harvesting the potential of this approach, we established hiPSC-derived human-human neuronal cocultures that not only allow for independent manipulation of each coculture partner but also resulted in morphologically more mature iNs. In summary, we exploit hiPSC-based methods to facilitate the analysis of human somatic cell-to-neuron conversion.
CRIS-Team Scopus Importer:2023-11-03
Keywords: direct lineage reprogramming; induced neurons; organoids; pericytes